ANALISIS SEKTOR TERTINGGAL DI KABUPATEN KERINCI MENGGUNAKAN METODE LQ DAN DLQ - Lisa Permata Sari; Ahmmad Syukron Prasaja (Jurnal Ekonomi & Bisnis, 2023)
Running the development with limited resources needs to focus on developmental sectors having multiple effects to the other sectors or to the entire economy. The result of DLQ shows that sectors such as transportation and communication, gas, electricity, clean water, finance, leasing and business services, mining and quarrying, trade, hotels and restaurants, as well as the service sectors that has DLQ value > 1 are are prospective to drive development as an effort to promote and encourage the regional economy. These sectors are also capable in competing with the same economic sector outside the Regency of Kerinci. The results of this study indicate that which is the base sector and has the potential to be developed to support the economy of the Kerinci Regency area with the criteria of being classified as an advanced and rapidly growing sector, the basic and competitive sector, namely the agricultural sector, the water supply sector, waste management, waste and recycling re, real estate sector, health services sector and social activities. The agricultural sector is superior because it contributes the most to the Gross Regional Domestic Product (GRDP) of Kerinci Regency. The agricultural sub-sector that has the potential to be developed as a lagging sub-sector.